2020
DOI: 10.1108/rege-05-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sustainable innovation and product or service innovation: a survey in companies in Rio Grande do Sul

Abstract: PurposeEnvironmental problems and natural resources scarcity are changing contemporary organizations management. The current society quest sustainable companies, mostly concern with the consumption and efficient management of natural resources; those innovative and sustainable companies have the capacity to create innovations and beneficial outcomes for the environment and society. The purpose of this paper is to analyze the relevance of sustainable innovation on products and services innovation, in companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The results of this research are in accordance with the results of previous research, which was conducted by Thi et al (2023), Phung et al (2021);and Severo et al (2020). Thus, it can be concluded that innovation strategies through innovation processes and systems can increase sustainable competitive advantage.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The results of this research are in accordance with the results of previous research, which was conducted by Thi et al (2023), Phung et al (2021);and Severo et al (2020). Thus, it can be concluded that innovation strategies through innovation processes and systems can increase sustainable competitive advantage.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The orientation of sustainable development (or green economy) around the "three E's" (environmental protection, economic growth and social justice) is also linked to considerations of quality of life [38]. It benefits the economy of the region socially, environmentally and economically as it provides better ways to use resources or eliminate environmental pollution and ecological growth of the region [39]. The green economy is interpreted as the 4Rs-i.e., reduction, reuse, recycling and recovery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TBL‐based sustainability concept adopts a broader focus and pursues the economic, social, and environmental dimensions altogether (Zubeltzu‐Jaka et al, 2018). Hitherto, researchers have been focusing on the environmental dimension and continuously overlooked the social dimension while studying the sustainable innovation construct (e.g., Delmas & Pekovic, 2018; Hernandez‐Vivanco et al, 2018; Severo et al, 2020). Therefore, under the TBL approach, it is imperative to combine the social dimension with the environmental dimension in the aggregate SPA.…”
Section: Literature Reviewmentioning
confidence: 99%